The Impact of Mindfulness as a Session‐Introduction on Symptoms and Alliance in Individual Cognitive‐Behavioral Therapy With Children and Adolescents: A Randomized Controlled Trial - Julia Kalmar; Ines Baumann; Elena Schleiting; Anne Grünert; Eva Vonderlin; Katajun Lindenberg; Andreas B. Neubauer; Thomas Heidenreich; Johannes Mander (Journal of Clinical Psychology, 2026)
ABSTRACT Objectives Mindfulness is increasingly being implemented in child and adolescent therapy. However, little is known about its effectiveness in individual settings within a clinical outpatient context. We investigated the effects of session‐introducing mindfulness interventions (IG‐M) compared to session‐introducing relaxation interventions (CG‐R) and no standardized session‐introduction (CG) on symptomatic outcome and therapeutic alliance in cognitive‐behavioral therapy using a randomized controlled design. Method One thousand four hundred and seventy‐eight of 90 outpatient adolescents (11–19 years) diagnosed with depression, an anxiety disorder, or a hyperkinetic disorder were assessed. Symptomatic outcome was assessed by the German version of the Youth Self‐Report 11‐18R at five measurement time points (pre, 3rd, 10th, 17th therapy session, post), therapeutic alliance was assessed by the German version of the Therapeutic Alliance Scales for Children after every therapy session (1st–24th therapy session). Statistical analyses were conducted using multilevel modeling. The RCT was registered at ClinicalTrials.gov (NCT04034576). Results Multilevel modeling revealed a significant decrease of symptomatic outcome in IG‐M compared to CG, but not compared to CG‐R, over time. A significant increase in therapeutic alliance over time was observed from the therapists' perspective with no group differences. Therapeutic alliance from patients' perspective significantly increased in IG‐M and significantly decreased in CG. There was no statistically meaningful change in therapeutic alliance from the patients' perspective in CG‐R. Conclusion IG‐M had positive effects on symptomatic outcome and therapeutic alliance compared to CG, but did not outperform CG‐R. Future studies that control confounding variables are highly relevant to understand the role of mindfulness in individual youth psychotherapy.